What retirees want : a holistic view of life's third age - Dychtwald, Ken, 1950-; Morison, Robert (John Wiley & Sons, Inc., 2020)
The authors explore the new retirement as people live longer lives, including work, leisure, health, family, home, finances, and purpose. "The world is witnessing a powerful new version of retirement, driven by the power and needs of the Baby Boomer generation. Consumers over age 50 account for more than half of all spending and control more than 70% of our total net worth -- yet are largely ignored by youth-focused marketers. How will work, family, and retirement be transformed to accommodate two billion people over the age of 60 worldwide? In the coming years, we'll see explosive business growth fueled by this unprecedented longevity revolution... This exciting new stage of life, the "Third Age," poses daunting questions: What will 'old' look like in the years ahead? With continued advances in longevity, all of the traditional life-stage markers and boundaries will need to be adjusted. What new products and services will boom as a result of this coming longevity revolution? ... Dychtwald and Morison explain how individuals, businesses, non-profits, and governments can best prepare for a new era."--Amazon.com.